Oxidative stress in patients with endemic pemphigus foliaceus and healthy subjects with anti-desmoglein 1 antibodies - Gutierrez, Ericson Leonardo (2018)
Background: Previous studies have shown oxidative stress in pemphigus vulgaris and pemphigus foliaceus, nevertheless, it remains unknown whether a similar response is characteristic of endemic pemphigus foliaceus in Peru. Objectives: To determine the oxidative stress response in endemic pemphigus foliaceus patients and subjects with positive for anti-desmoglein1 antibodies (anti-dsg1) from endemic areas of Peru. Subjects and Methods: This is a cross-sectional study. The study population included 21 patients with Endemic Pemphigus foliaceus and 12 healthy subjects with anti-dsg1 antibodies from the Peruvian Amazon (Ucayali), as well as 30 healthy control subjects. Malondialdehyde, an indicator of lipid peroxidation by free radicals, was measured in serum. Results: We collected 21 cases of endemic pemphigus foliaceus, 15 of them with active chronic disease and 6 in clinical remission. Serum malondialdehyde values in patients with chronic active evolution and healthy subjects with anti-dsg1 antibodies were statistically higher than those of healthy controls (p<0.001). There was no significant difference between serum values of localized and generalized clinical forms. Study limitations: The main limitation of this present study is the small number of patients with endemic pemphigus and healthy subjects positive for desmoglein 1 antibodies. Conclusions: The increased serum levels of malondialdehyde in patients with chronic active endemic pemphigus foliaceus and healthy subjects from endemic areas with anti-dsg1 antibodies may suggest a contribution of systemic lipid peroxidation in the pathogenesis of endemic pemphigus foliaceus.